A Systematic Bibliometric Review on Metaverse as a Disruptive Technology Reforming Destination Marketing Practices - Adhikari, Ujjawal (Janapriya Journal of Interdisciplinary Studies, 2024)
In recent years, the role of technology in improving information and communication within the hospitality industry has evolved significantly and is considered one of the strategic resources that enable enterprise businesses to shape superior customer experiences by becoming more engaging and informative. Due to shifting consumer behavior-where an ever-increasing amount of consumers seek to purchase on the internet-the current paper examines the use of the metaverse for destination marketing and builds a base for further research into this aspect. Through a bibliometric analysis of articles indexed in WoS, this study identifi es the emergent themes, the structure of the field, and the collaboration patterns. A systematic review of the selected 15 articles which are refined through the PRISMA model with a Boolean proximity search strategy is presented. Bibliometric maps were constructed using the VOSviewer software. The findings also prove that the development of metaverse tourism enhances the attractiveness of destinations by adding more value to the tourist experience. Digital activities in the metaverse provide much-needed insights into customer needs and preferences, thus enabling proactiveness in engaging and informed decision-making.